PENGARUH VARIASI ARUS GAS METAL ARC WELDING (GMAW) TERHADAP KEKUATAN TARIK SAMBUNGAN T-JOINT PADA CROSSMEMBER BAJA JIS G3101 SS400 - Naufal, Kato Ra'if; Yongkimandalan, Nicky (Badan Penerbit Universitas Muria Kudus, 2026)
Welded joints in vehicle chassis structures, particularly the connection between crossmembers and longitudinal members, play a critical role in ensuring structural integrity and load-bearing performance in commercial vehicles. This study aims to analyze the effect of welding current variation in the Gas Metal Arc Welding (GMAW) process on the tensile strength of T-joint welds made of JIS G3101 SS400 steel applied to ladder frame crossmembers. Welding was performed using ER70S-6 filler wire with a diameter of 1 mm under three different current settings: 72 A, 85 A, and 104 A. Other welding parameters, including welding speed and welding position, were maintained constant to ensure experimental consistency and isolate the influence of current variation. The welded specimens were subjected to tensile testing using a Universal Testing Machine (UTM) until failure in order to obtain maximum load capacity, tensile stress, and deformation characteristics. The experimental results indicate that welding current significantly influences the mechanical performance of the welded joint. The 85 A current produced the highest maximum load of 130.4 kN and an ultimate tensile strength of 434.83 MPa, indicating optimal penetration and fusion quality. At 72 A, insufficient heat input resulted in lower penetration and reduced tensile strength. Conversely, the 104 A current introduced higher heat input, which increased the width of the heat-affected zone and showed a tendency toward localized distortion. Based on the analysis, it can be concluded that a welding current of 85 A represents the optimal parameter for the joint configuration and material used in this study. These findings provide practical recommendations for chassis fabrication and repair processes to improve structural reliability and tensile performance